BASLAWÍSh KLASS OQÍWShÍLARÍNÍŃ OQÍW KÓNLIKPELERIN JETILISTIRIWDE PÁN DÓGEREKLERINIŃ ORNÍ - Turumbetova, Aygul Yusupbaevna (SCIENCE and SOCIETY, 2026)
This article examines the role of science clubs in improving primary school students' academic skills and increasing their interest in education. It provides information on interest in books at the early stages of the primary education system, beginning in elementary school and adolescence.